Comparative Analysis of the Application of Multilayer and Convolutional Neural Networks for Recognition of Handwritten Letters of the Azerbaijani Alphabet - Mustafayev, E.; Azimov, R. (Кібернетика та комп’ютерні технології, 2021)
The implementation of information technologies in various spheres of public life dictates the creation of efficient and productive systems for entering information into computer systems. In such systems it is important to build an effective recognition module. At the moment, the most effective method for solving this prob-lem is the use of artificial multilayer neural and convolutional networks. This paper is devoted to a comparative analysis of the recognition results of handwritten characters of the Azerbaijani al-phabet using neural and convolutional neural networks. The results of numerical experiments are given. Мета роботи. Провести порівняльний аналіз результатів розпізнавання рукодрукованих символів азербайджанського алфавіту за допомогою багатошарових і згорткових нейронних мереж. Результати. Проведено аналіз залежності результатів розпізнавання від наступних параметрів: архітектури нейронних мереж, розміру навчальної бази, вибору алгоритму субдискретизації, використання алгоритму виділення ознак. Для збільшення навчальної вибірки використана техніка аугментації зображень. На основі реальної бази з 14000 символів були утворені бази по 28000, 42000 і 72000 символів. Наведено опис алгоритму виділення ознак. Цель работы. Провести сравнительный анализ результатов распознавания рукопечатных символов азербайджанского алфавита с помощью многослойных и сверточных нейронных сетей. Результаты. Проведен анализ зависимости результатов распознавания от следующих параметров: архитектуры нейронных сетей, размера обучающей базы, выбора алгоритма субдискретизации, использования алгоритма выделения признаков. Для увеличения обучающей выборки использована техника аугментации изображений. На основе реальной базы из 14000 символов были образованы базы по 28000, 42000 и 72000 символов. Приведено описание алгоритма выделения признаков.